Fiscal Consolidation and Firm Level Productivity : Evidence from Advanced Economies - Tuuli, Maxwell (IMF Working Papers; Working Paper ;, 2022)
Productivity dispersion across countries has led to several studies on the determinants of firm level productivity and the role of macroeconomic policies in determining productivity. In this paper, we investigate the effect of fiscal consolidation on firm level productivity in 12 advanced economies by combining an updated dataset of fiscal consolidation measures with firm level productivity. We find that fiscal consolidation (i.e., discretionary tax hikes and spending cuts), is detrimental to firm level productivity in advanced economies. We also find that high levels of fiscal consolidation are particularly harmful to firm level productivity compared to lower levels of fiscal consolidation. Furthermore, we find that tax based fiscal consolidation hinders firm level productivity more compared to spending based fiscal consolidation. This implies that the size and composition of fiscal consolidation matter in understanding the relationship between fiscal consolidation and firm level productivity.